Thoracoabdominal Asynchrony Contributes to Exercise Limitation in Mild Asthmatic Subjects - Fregonezi, Guilherme; Sarmento, Antonio; Pinto, Janaína; LoMauro, Antonella; Resqueti, Vanessa; Aliverti, Andrea (Frontiers in Physiology, 2018)
This study aimed to better understand how subjects with stable asthma and without exercise-induced bronchoconstriction respond to mild exercise. Breathing pattern, chest wall compartmental and operational volumes and thoracoabdominal asynchrony were assessed in 11 stable asthmatic subjects and 10 healthy at rest and during exercise in a cycle-ergometer through optoelectronic plethysmography. Dyspnea and sensation of leg effort were assessed through Borg scale. During exercise, with similar minute ventilation, a significant lower chest wall tidal volume (p=0.003), as well as a higher respiratory rate (p<0.05) and rapid shallow breathing (p<0.05) were observed in asthmatic when compared to healthy subjects. Asthmatic subjects exhibited a significantly lower inspiratory (p<0.05) and expiratory times (p<0.05). Intergroup analysis found a significant higher end-expiratory chest wall volume in asthmatic subjects, mainly due to a significant increase in volume of the pulmonary ribcage [RCp] (170 ml, p=0.002), indicating dynamic hyperinflation (DH). Dyspnea and sensation of leg effort were both significantly greater (p<0.0001) in asthmatic when compared to healthy subjects. In addition to a higher thoracoabdominal asynchrony found between RCp and abdominal (AB) (p<0.005) compartments in asthmatic subjects, post-inspiratory action of the inspiratory ribcage and diaphragm muscles were observed through the higher expiratory paradox time of both RCp (p<0.0001) and AB (p=0.0002), respectively. Our data suggest that a different breathing pattern is adopted by asthmatic subjects without exercise-induced bronchoconstriction during mild exercise and that this feature, associated with DH and thoracoabdominal asynchrony, contributes significantly to exercise limitation.